Scale of perceived exertion as injury prevention tool for young football players - A. V. Borisova; F. V. Takhavieva; M. M. Kuznetsova; I. S. Dolgalev; Y. I. Preobrazhensky; Z. O. Shabanova; E. A. Malyakina; M. S. Butovsky (National Electronic Information Consortium (NEICON), 2024)
Objective: evaluation of the feasibility of using the Borg CR10 perceived exertion scale in the training process of young football players and its role in injury prevention.Material and methods: 48 athletes aged 15-17 were examined by scale of perceived exertion during the 7 month every day within 20 minutes after the training. The coaches also assessed the degree of perceived exertion. A comparative retrospective analysis of injuries was done for the periods of the mycrocycle of the youth football league of the seasons 2020-2021 and 2021-2022 based on muscle injuries, ligament and joint capsular injuries.Results: Athletes' scores on the Borg CR10 scale in the preparation, competition and transitional stages of the competitive macrocycle are 5.08 ± 1.28, 5.00 ± 1.16 and 4.67 ± 1.38, respectively. The coaches' scores for the aforementioned periods are 4.78 ± 0.89, 5.09 ± 1.05 and 4.82 ± 0.99. The total scores of players and coaches is 5.20 ± 1.85 and 4.96 ± 1 respectively. Moreover, there is no statistically significant difference between the rate of perceived exertion between players and coaches for the whole season (p = 0.288).There is a decreased injury rate in young professional athletes group when the Borg CR10 scale of perceived exertion is measured in a season with the use of this scale compared to a season where the Borg CR 10 scale was not used (p = 0,028).Conclusion: the Borg СR10 scale is a useful methodology for assessing the level of perceived exertion of a young athlete and can be used for early training corrections in order to reduce injuries.